Devan Kallas: capstone - Kallas, Devan, artist (Colorado State University. Libraries, 2016)
The artist's statement: My works are tied together by the line of intimacies and are deducted by the space of neglect. They take various forms and range in topic but all stem from a sense of self and emphasize importance of the temporary. I am motivated by the boundaries of a contemporary self, pushing and poking at the limits of comfort, if it's not made with an uncertainty it is not made at all. Most recently my art has seeded from a politically charged idea and manifested itself with a poetic movement. Each piece has a specific motivation and intent; I believe each is made with purpose not just simple aesthetic appeal.
It's only temporary
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing; sculpture; installation; performance